Pathological Narcissism and Emotional Responses to Rejection: The Impact of Adult Attachment - Reis, Samantha; Huxley, Elizabeth; Eng Yong Feng, Bryan; Grenyer, Brin F. S. (Frontiers in Psychology, 2021)
Background: Aspects of pathological narcissism, such as grandiosity, vulnerability and entitlement, tend be enacted in therapeutic settings, negatively influencing outcome and alliance between the clients and therapist. This research took an experimental approach to understanding the interplay between the emotional reactions of individuals with a pathological narcissistic presentation, and adult attachment style. We predicted that participants reporting narcissistic vulnerability would report greater insecurity in attachment (fearful and preoccupied styles), greater trait emotional reactivity, and also experience more intense and negative responses to simulated rejection Methods: 269 participants (75.84% female, median age = 21) completed baseline and rejection trials of a virtual ball-tossing game, following the assessment of grandiose and vulnerable pathological narcissism, entitlement, adult attachment, trait emotional reactivity (measured prior to the rejection) and in-situ affective response (measured both before and after the rejection). Change in affect from baseline was calculated to capture affective responses to the manipulation. Results: Vulnerable narcissism was positively associated with both fearful and preoccupied attachment, and negatively associated with secure and dismissive attachment, whilst grandiose narcissism was significantly related to preoccupied attachment only. Multiple hierarchical regression analyses showed vulnerable narcissism predicted both (1) more negative trait emotional reactivity and (2) a significant increase in negative affect following the rejection trial. Grandiose narcissism was associated with (1) higher positive trait emotional reactivity, and (2) significant reductions in positive affect following rejection. Conclusion: Results indicated that those high in pathological narcissistic vulnerability reported greater insecurity in attachment, negative trait emotional reactivity and experienced a more negative and intense emotional reaction to rejection. Grandiose narcissism was related to a more deactivated pattern of emotional reactivity, and less positive (rather than more negative) emotional reactions. Findings have important implications for therapy, particularly regarding communication of emotions for individuals high in vulnerable and grandiose narcissism.